Race for revival: how Cold War South Korea shaped American Evangelical empire - Kim, Helen Jin (Oxford scholarship online, 2022)
"In 1973, Billy Graham, "America's Pastor," held his largest ever "crusade." But he was not, as one might expect, in the American heartland, but in South Korea. Why there? Race for Revival seeks not only to answer that question, but to retell the story of modern American evangelicalism through its relationship with South Korea. With the outbreak of the Korean War, the first "hot" war of the Cold War era, a new generation of white fundamentalists and neo-evangelicals forged networks with South Koreans that helped turn evangelical America into an empire. South Korean Protestants were used to bolster the image of the US as a non-imperial beacon of democratic hope, in spite of ongoing racial inequalities. At the same time, South Koreans used these racialized transpacific networks for their own purposes, seeking to reimagine their own place in the world order. They envisioned Korea as the "new emerging Christian kingdom," that would beat the American evangelical empire in a race for revival. Yet these nonstate networks ultimately foreshadowed the rise of the Christian Right in the US and South Korea in the 1980s and 1990s. Employing a bilingual and bi-national approach, Race for Revival reexamines the narrative of modern evangelicalism through an innovative transpacific framework, offering a new lens through which to understand evangelical history from the Korean War to the rise of Ronald Reagan"--